Preliminary genetic linkage map of the abalone Haliotis diversicolor Reeve - 石耀华 郭希明 顾志峰 王爱民 王嫣 (Chinese journal of oceanology and limnology, 2010)
Haliotis diversicolor Reeve is one of the most important mollusks cultured in South China. Preliminary genetic linkage maps were constructed with amplified fragment length polymorphism （AFLP） markers. A total of 2 596 AFLP markers were obtained from 28 primer combinations in two parents and 78 offsprings. Among them, 412 markers （15.9%） were polymorphic and segregated in the mapping family. Chi-square tests showed that 151 （84.4%） markers segregated according to the expected 1：1 Mendelian ratio （P〈0.05） in the female parent, and 200 （85.8%） in the male parent. For the female map, 179 markers were used for linkage analysis and 90 markers were assigned to 17 linkage groups with an average interval length of 25.7 cm. For the male map, 233 markers were used and 94 were mapped into 18 linkage groups, with an average interval of 25.0 cm. The estimated genome length was 2 773.0 cm for the female and 2 817.1 cm for the male map. The observed length of the linkage map was 1 875.2 cm and 1 896.5 cm for the female and male maps, respectively. When doublets were considered, the map length increased to 2 152.8 cm for the female and 2 032.7 cm for the male map, corresponding to genome coverage of 77.6% and 72.2%, respectively.